Public preferences for policy intervention to protect public health from maritime activities: A 14 European country study. (November 2021) - Roberts, B.R.; White, M.P.; Davison, S.M.C.; McMeel, O.; Eatock, C.; Kellett, P.; Calewaert, J.-B.; Fleming, L.E.
Highlights: European public are aware of the economic benefits of maritime activities. Potential link observed between perceived impact on the environment and on human health. Cross-country differences highlight need for tailored communications and policies. Abstract: Marine ecosystems provide a wide range of goods and services that directly and indirectly benefit economies and support human health and wellbeing. However, these ecosystems are vulnerable to anthropogenic influences such as climate change, pollution and habitat destruction. The European Union (EU) recognises the role of the blue economy in providing jobs and contributing to economic growth, with the EU Integrated Maritime Policy being a cross-sectoral framework within which maritime activities are managed and coordinated. Sustainability is a central tenet, ensuring that sectors such as aquaculture and offshore wind energy, which are earmarked for growth, must develop in ways that do not negatively impact the health of the marine environment. However, there is currently little consideration of how these activities might impact public health. The current research used survey data from 14 European countries to explore public perceptions of these issues, broadly focusing on 10 maritime activities, with a specific focus on five activities related to the EU's 2012 Blue Growth Strategy. The respondents appreciated the interconnections between these maritime activities, environmental protection and public health, as well as the potential trade-offs. Preferences for policy intervention to protect public health from different activities were predicted by both marine contact (marine sector employment, recreational activities) and socio-demographic (political attitudes, gender, age) variables, potentially aiding future engagement and communication initiatives. Substantive differences observed across countries in terms of policy preferences for different activities, however, warn against generalising for the European population as a whole.